Environmental conflict : in search of common ground - Pompe, Jeffrey J., 1951- (State University of New York Press, 2002)
Annotation This straightforward translation of environmental economics discusses issues and concerns that have long-lasting and often substantial effects. The authors bridge the gap between the natural and social sciences by examining how economic decisions interact with the environment. In addition, they explain why economics plays an important role in clarifying environmental issues and formulating solutions. Environmental Conflict analyzes policy choices and provides a basic methodology for understanding a broad range of environmental topics. These include the tragedy of the commons, the importance of incentives and markets, the role of government, property rights, benefit-cost analysis, natural resource use, pollution control, economic growth, international trade, global warming, and biodiversity loss.
Includes index.
Keywords: Environmental policy -- Economic aspects.; Environmental protection -- Economic aspects.; Environnement -- Politique gouvernementale -- Aspect économique.; Environnement -- Protection -- Aspect économique.; BUSINESS & ECONOMICS -- Development -- Sustainable Development.; NATURE -- Environmental Conservation & Protection.; Environmental policy -- Economic aspects; Environmental protection -- Economic aspects; Includes index.; Multi-User